Simulation modeling tools in training environmental science students - А. G. Kot; A. B. Achasov; O. Yu. Seliverstov; V. G. Karpov (Вісник Харківського національного університету імені В.Н. Каразіна: Серія Екологія)
The use of computer modeling and forecasting for the analysis and prediction of complex systemic processes, particularly in the field of environmental protection, is extremely important. For students of ecological specialties, proficiency in modeling is a key aspect. There are at least two computer simulation programs available on the market with free versions for student education: VensimPLE and AnyLogicPLE. They enable the use of simulation modeling and system dynamics for analyzing and predicting ecological processes. Students are provided with the opportunity to create and study various scenarios using mathematical models. Students are encouraged to create and investigate the "Predator Prey" model, which is based on the Volterra-Lotka system of differential equations. The model describes the dynamics of predator and prey populations in a closed and stationary system. Based on equations that consider the reproduction and mortality of both species, students need to explore the interaction between populations under different input parameters. The model has two stages: initially, accumulators with initial population values are created, then parameters regulating flows are added. Using the example of the provided model, the possibility of studying the impact of various factors on ecosystem dynamics and understanding it more deeply is highlighted.